Transposition of the Thinking Classroom approach: cultural and institutional factors - Pocalana, Gabriella; Liljedahl, Peter (LUMAT-B: International Journal on Math, Science and Technology Education, 2025)
In this paper, we investigated the cultural transposition of the Thinking Classroom approach to the teaching and learning of mathematics in the context of a professional development program for in-service Italian teachers. This approach, originating from a different cultural context, diverged in many aspects from the usual practices of Italian teachers. The participants in our study are 17 (lower- and upper-) secondary school mathematics teachers following the program for the second year. We collected data from a written anonyms questionnaire with open and Likert-scale questions about teachers’ evaluation of various aspects of the Thinking Classroom approach. We conducted a qualitative content analysis of teachers’ answers, from which we derived three main emerging themes: Affect, Method, and Task and mathematical content. From a cross analysis of these themes, several teachers’ unthoughts about mathematics teaching and learning approaches emerged, which we relate to both cultural and institutional characteristics of the Italian school system.